Sistem Penunjang Keptusan Pemilihan Internet Service Provider Di Salatiga Dengan Menggunakan Metode Fuzzy MADM - Dwi Agus Diartono; Teguh Khristianto; THD. Wismarini; Hari Murti; R. Soelistijadi (LPPM STIKOM Tunas Bangsa, 2023)
The Fuzzy MADM method is used to deal with uncertainty and ambiguity in decision-making. This method considers several relevant attributes in the selection of an Internet Service Provider (ISP), such as internet speed, package price, service availability, and network reliability. Each attribute is assigned a weight based on its level of importance determined by the user. In this study, data on the performance of different ISPs were collected and analyzed. Fuzzy MADM was used to process the data and provide recommendations for selecting the most suitable ISP according to user preferences. The developed decision support system allows users to adjust attribute weights according to their needs and preferences. The decision support system for selecting an Internet Service Provider using the Fuzzy MADM method identifies three alternatives and four evaluation criteria: price, security, satisfaction, and credibility. This system can be used to recommend an Internet Service Provider in Salatiga based on the needs and desires of the users, employing the Fuzzy MADM method to find the appropriate ISP